The Effect of Drying on Anthocyanin Content and Antioxidant Activity in Red Cabbage and White Cabbage - Rahmat Efendi; Rahmandika Irfan Pradana; Luthfi Kurnia Dewi; Chandrawati Cahyani (Reaktor, 2022)
Red cabbage and white cabbage contain several beneficial compounds, such as anthocyanins that can scavenge free radicals. The study aimed to determine the effect of drying on anthocyanin content and antioxidant activity in red cabbage and white cabbage. Each cabbage will be given two pretreatments, namely: (1) drying, and (2) without drying. Maceration extraction using a mixture of water and methanol 50:50 (v/v) acidified with 7% citric acid with a liquid to solid mass ratio of 1:4 (w/v) and with a controlled temperature of 60°C for a period of 1 h. Cabbage extract was examined for anthocyanin content by differential pH method and antioxidant activity was tested by DPPH method. The results showed anthocyanin content in crude fresh red cabbage extract 64.124 mg/L, crude dried red cabbage extract 210.74 mg/L, crude fresh white cabbage extract 0.445 mg/L, crude dried white cabbage extract 0.584 mg/L. The antioxidant activity (IC50) of crude fresh red cabbage extract, crude dried red cabbage extract, crude fresh white cabbage extract, and crude dried white cabbage extract were 54,317 ppm, 49,464 ppm, 131,878 ppm, and 107,069 ppm, respectively. The optimum results were crude dried red cabbage extract with a yield of 25.2%, anthocyanin content of 210.74 mg/L, IC50 value of 49.464 ppm.